GAMBARAN TINGKAT HARGA DIRI SISWA YANG MENGALAMI KEKERASAN VERBAL ORANG TUA DI SEKOLAH MENENGAH KEJURUAN - Rahmayada, R; Gutji, Nelyahardi; Zubaidah, Z (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This research aims to determine the level of self-esteem from students who experience verbal abuse which includes aspects of self-confidence and self-love at SMK Negeri 4 Jambi City. This research uses quantitative methods with a descriptive approach. The population in this study was class XI of SMK Negeri 4 Jambi City for the 2023/2024 academic year with a total of 424 students. The sampling technique was purposive sampling, namely 39 students who experienced verbal abuse from their parents. The data collection technique uses a self-esteem questionnaire and is processed using a percentage formula. The results of research on the level of self-esteem form students who experienced verbal violence from their parents at SMK Negeri 4 Jambi City showed that it was at a moderate level, namely 48.88%. With details on (1) the level of self-esteem of students who experienced verbal violence from their parents in the aspect of self-confidence at SMK N 4 Jambi City showed a moderate level, namely 46.20% (2) the level of self-esteem of students who experienced verbal violence parents in the aspect of self-love at SMK Negeri 4 Jambi City showed a moderate level of 51.87%. The results of this research show that the self-esteem of students who experience verbal abuse from their parents has positive self-acceptance but in a social environment it is possible to become an individual who is dependent on other individuals, which creates a feeling of insecurity. The results of this research can provide advice to schools, especially guidance and counseling teachers, so that the results of this research become a reference source in providing assistance to students who experience verbal violence by their parents by providing appropriate services.